The The Influence of Financial Literacy and Financial Behavior on the Financial Well Being of UMKM Players in the Tourism Sector in Madura - saidah, Arifatus; Purnamawati, Purnamawati; Gitayuda, M. Boy Singgih (Universitas Islam Lamongan, 2024)
The purpose of this study is to determine how Financial Literacy and Financial Behavior affect the Financial Well Being of MSME players in the tourism industry in Madura. MSMEs or small and medium enterprises are people's economic businesses that need to be protected from unfavorable business competition. MSMEs have a significant influence on the Indonesian economy. Although the name is associated with small and medium enterprises. In this study, research questionnaires were distributed to tourism MSMEs in Madura. Which is located in the Bangkalan Regency and Sampang Regency areas. With a quantitative approach using primary data. This study took a sample of 60 MSME players. SPSS Version 26 was used to test this research. The findings of this study indicate a beneficial impact of Financial Literacy (X1) and Finnacial Behavior (X2) on Financial Well Being (Y).